AUDIT DELAY DAN OPINI AUDIT - Alaudin Johari, Sidqi; Firman Alkausar, Muhammad; Sulhani, Sulhani (Jurnal Ilmiah Akuntansi dan Keuangan (JIAKu), 2025)
Audit delays of financial reports and opini audit can affect investor confidence and the credibility of a company’s financial reports. This study aims to analyze audit delays and opini audit of PT Adhi Karya (Persero) Tbk from 2018 to 2022. The research method used is a descriptive analysis based on literature review and secondary data from the company’s financial reporting, independent auditor reports, and relevant regulations. The findings indicate that PT Adhi Karya consistently received an Unqualified Opinion (WTP) that shows the quality of financial reporting of PT Adhi Karya,Meanwhile, regarding audit delay, during the analysis period, PT Adhi Karya only experienced an audit delay exceeding the regulatory limit in 2019 due to project complexity and the impact of COVID-19, as well as the absence of an audited financial report for 2021, coinciding with changes in the Audit Committee structure. The primary factors contributing to audit delays include large-scale construction projects, changes in accounting regulations, and external challenges such as the pandemic. The study highlights the importance of strengthening internal audit governance and monitoring financial reporting to reduce audit delays and enhance transparency and stakeholder trust